Effective Social Work Online Education in Response to COVID-19. Issue 5 (20th October 2021) - Jun, Jung Sim; Kremer, Kristen P.; Marseline, Debra; Lockett, Lorenza; Kurtz, Don L.
ABSTRACT: Online education has shown consistent growth in social work curricula over the past two decades despite some questions about the effectiveness of virtual environments in teaching critical elements of social work practice and professional competency. With the COVID-19 pandemic, programs have been forced to exclusively utilize online teaching formats. This study explores student and field instructors' perceptions of the most effective teaching practices during the transition to online teaching. Findings indicate that students preferred asynchronous course content, such as recorded class lectures and discussion boards to live discussions and lectures because of its flexibility. Students completing the practicum process observed significant disruption to traditional social work education, although both students and field supervisors adapted by allowing increased use of video conferencing and telephone practice. Findings indicate clear student preferences and could foster ways to improve e-learning in the future.